Pembuatan Grafena dengan Metode Reduksi Graphene Oxide Menggunakan Bahan Baku Grafit dan Reduktor Natrium Hipopospit - Ratna Sari; Cut Dina Mastura; Teuku Rihayat; Ratni Dewi; Lukman Hakim (Jurnal Serambi Engineering, 2022)
One of the new materials that has developed recently is graphene. Graphene is a new closed, strongest, and superior material in the world today which is formed from a single layer of carbon atoms which has a hexagonal structure resembling a honeycomb. This study aims to determine the effect of graphite size on the quality of graphene produced using the graphene oxide reduction method. This method uses sodium hypophosphite reductor and oxidizing agent KMnO4, sulfuric acid and hydrogen peroxide. The quality of graphene is observed by looking at the electrical conductivity produced. This study varied the size of the graphite (106 µm, 125 µm, 150 µm, 180 µm dan 250 µm) and the reductor volume variation (3 ml, 5 ml, 7 ml, 9 ml dan 11 ml). The graphene oxide solution was heated in hot water and then filtered, ultrasonically for 3 hours, and in the oven for 6 hours at 80oC. From the results of the electrical conductivity test, the best results were obtained at a graphite size of 106 µm while for the volume of the reductor the best results were at 11 ml. Graphene was characterized using FTIR (Fourier transform infrared) and SEM (scanning electron microscope). The results of the characterization of the powder samples show that there has been a change in the structure of graphite to graphene. The size of the graphite and the volume reducing agent has a significant effect on the graphene’s electrical conductivity.